The effect of leg muscle explosiveness, waist flexibility, and hand-eye coordination on the precision of volleyball athletes' smash accuracy girls in the Padang Adios club - Ryzki Adilla; Ishak Aziz; Muhamad Sazeli Rifki; Yendrizal Yendrizal; Fiky Zarya (Jorpres (Jurnal Olahraga Prestasi), 2023)
The purpose of this study was to determine the direct and indirect influence of leg muscle explosiveness, waist flexibility, and eye-hand coordination on smash accuracy. This type of research is correlational using the path analysis method. The population in this study was Padang Adios volleyball athletes, sampling using purposive sampling totaling 25 female athletes. The test instruments used are, vertical jump, sit and reach test, throw catch the ball, and accuracy of smash accuracy. Data analysis technique using Path Analysis with α = 0.05. The results of the study were (1) There was a direct influence of leg muscle explosive power on smash accuracy, with r-count results of 0.879 r-table 0.404. (2) There is an indirect effect of waist flexion on smash accuracy, with r-count results of 0.360 r-table 0.404. (3) There is a direct effect of eye-hand coordination on smash accuracy, with r-count results of 0.664 r-table 0.404. (4) There is a direct effect of leg muscle explosive power on smash accuracy through eye-hand coordination, with pyx3 results of 0.720 0.404. (5) There is an indirect influence of waist flexion on the accuracy of the volleyball smash of the Padang Adios club through eye-hand coordination. This can be seen from the results of pyx4 0.068 0.404. (6) There is a simultaneous influence of joint influence between leg muscle explosiveness, waist flexibility, and eye-hand coordination on the accuracy of the volleyball smash of the Padang Adios club. It is proven that the explosive power of the leg muscles has a greater influence to increase the accuracy of volleyball smashes, with a percentage result of 19.36%. It was concluded that there was an influence of leg muscle explosive power, waist flexibility, and eye-hand coordination on smash accuracy.